Human cerebral cortex Cajal-Retzius neuron: development, structure and function. A Golgi study - Marín-Padilla, Miguel (Frontiers in Neuroanatomy, 2015)
The development, morphology and possible functional activity of the Cajal-Retzius cell of the developing human cerebral cortex are explored herein. The C-RC, of extracortical origin, is the essential neuron of the neocortex first lamina. It receives inputs from afferent fibers that reach the first lamina early in development. Although the origin and function of these original afferent fibers remain unknown, their target is the first lamina sole neuron: the C-RC. This neuron orchestrates the arrival, size and stratification of all pyramidal neurons (of ependymal origin) of the neocortex gray matter. Its axonic terminals spread radially and horizontally throughout the entirety of the first lamina establishing contacts with the dendritic terminals of all gray matter pyramidal cells regardless of size, location and/or eventual functional roles. While the neuron axonic terminals spread radially and horizontally throughout the first lamina, the neuronal’ body undergoes progressive developmental dilution and locating any of them in the adult brain become quite difficult. The neuron bodies are probably retained in the older regions of the neocortex while their axonic collaterals will spread throughout its more recent ones and eventually will extend to great majority of the cortical surface. The neocortex first lamina evolution and composition and that of the C-RC are intertwined and mutually interdependent. It is not possible to understand the C-RC evolving morphology without understanding that of the first lamina. The first lamina composition and its structural and functional organizations obtained with different staining methods may be utterly different. These differences have added unnecessary confusion about its nature. The essential emptiness observed in hematoxylin and eosin preparations (most commonly used) contrast sharply with the concentration of dendrites (the cortex’ largest) obtained using special (MAP-2) stain for dendrites. Only Golgi preparations demonstrate the numerous dendritic and axonic terminals that compose the first lamina basic structure. High power microscopic views of Golgi preparations demonstrate the intimate anatomical and functional interrelationships among dendritic and axonic terminals as well as synaptic contacts between them. The C-RC’ essential morphology does not changes but it is progressively modified by the first lamina increase in thickness and in number of terminal dendrites and their subsequent maturation. This neuron variable morphologic appearance has been the source of controversy. Its morphology depends on the first lamina thickness that may be quite variable among different mammals. In rodents (most commonly used experimental mammal), the first lamina thickness, number and horizontal expansion of dendrites is but a fraction of those in humans. This differences are reflected in the C-RC’ morphology among mammals (including humans) and should not be thought as representing new types of neurons.